2013
DOI: 10.1073/pnas.1307595111
|View full text |Cite
|
Sign up to set email alerts
|

The signaling network that silences the spindle assembly checkpoint upon the establishment of chromosome bipolar attachment

Abstract: Improper kinetochore attachments activate the spindle assembly checkpoint (SAC) to prevent anaphase onset, but it is poorly understood how this checkpoint is silenced to allow anaphase onset. Chromosome bipolar attachment applies tension on sister kinetochores, and the lack of tension delays anaphase onset. In budding yeast, the delay induced by tension defects depends on the intact SAC as well as increase in ploidy (Ipl1)/Aurora kinase and a centromere-associated protein ShuGOshin (Sgo1). Here we provide evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
62
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 27 publications
5
62
0
1
Order By: Relevance
“…We showed that Ipl1 kinase and Sgo1 are required to prevent SAC silencing in response to syntelic attachment induced by CIK1-CC overexpression (Jin et al 2012;Jin and Wang 2013). Because the centromere localization of Sgo1 depends on H2A phosphorylation by Bub1 kinase (Fernius and Hardwick 2007;Kawashima et al 2010;Nerusheva et al 2014), Bub1 kinase activity might be required to prevent SAC silencing in response to syntelic attachment, although this kinase activity is dispensable for SAC activation (Fernius and Hardwick 2007).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…We showed that Ipl1 kinase and Sgo1 are required to prevent SAC silencing in response to syntelic attachment induced by CIK1-CC overexpression (Jin et al 2012;Jin and Wang 2013). Because the centromere localization of Sgo1 depends on H2A phosphorylation by Bub1 kinase (Fernius and Hardwick 2007;Kawashima et al 2010;Nerusheva et al 2014), Bub1 kinase activity might be required to prevent SAC silencing in response to syntelic attachment, although this kinase activity is dispensable for SAC activation (Fernius and Hardwick 2007).…”
Section: Resultsmentioning
confidence: 90%
“…The anaphase entry delay in dam1-3D mutants is alleviated by bub1-DK The phosphorylation of kinetochore protein Dam1 by Ipl1 kinase destabilizes kinetochore-microtubule attachment to facilitate correction (Pinsky et al 2006;Tien et al 2010), but the delayed anaphase entry in phospho-mimetic mutant dam1-3D is primarily attributed to its inability to silence the SAC (Jin and Wang 2013). Thus, we tested if the anaphase entry delay in dam1-3D requires the kinase activity of Bub1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations